The Democratic Party “Coup” between Agus Harimurti Yudhoyono and Moeldoko on Detik.com and Okezone.com - Febriyanti, Resya Fikriyah; Nuraeni, Reni (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2022)
At the beginning of 2021, the Democratic Party was burdened by the coup issue with the Extraordinary Congress (KLB) initiated by Jhoni Allen Marbun and company who produced the new Chairman of the Democratic Party, Moeldoko. The culmination of the Democratic Party leadership takeover case occurred when Minister Yasonna Laoly officially mentioned that the Democratic Party KLB had submitted the results of the KLB led by Jhoni Allen Marbun (one of the initiators of KLB). News of the coup carried out by Moeldoko against the Democratic Party has been widely highlighted by the mass media, especially online media such as Detik.com and Okezone.com. The study aimed to find out how the two media outlets framed the news of the Democratic Party coup case between Agus Harimurti Yudhoyono (AHY) and Moeldoko, researchers using Zhongdang Pan & Gerald M. Kosicki framing looked at the framing of syntactic, script, thematic and rhetorical structures. Researchers use the consumerist paradigm and qualitative research methods. Research results showed that Detik.com emphasized on cornering the Moeldoko party where the Democratic Party coup carried out by Moeldoko’s side was wrong and not right from the legal side, and many featured sources that were pro-AHY. Meanwhile, Okezone.com is more balanced and bolder in conveying criticism to Agus Harimurti Yudhoyono (AHY) so the two online media both Detik.com and Okezone.com have different ways of building opinions and perceptions of readers by looking at the issue of the coup carried out by the Moeldoko camp against the leadership of the Democratic Party and adjusting to what each of the media wants.